World Humanitarian Data and Trends 2015 - United Nations (United Nations, 2016)
This publication highlights major trends in the nature of humanitarian crises, their causes and drivers, and participation in crisis prevention, response and recovery. Beyond providing statistics, the trend analysis shows how the humanitarian landscape is evolving and how the humanitarian system can be more effective in a rapidly changing world. Data used in the report comes from a variety of sourcess. Highlights for 2015 include case studies on long-term trend analysis of the humanitarian context in terms of conflicts and natural disasters, the humanitarian footprint in the Middle East, coordination of online volunteers during the Ebola response and the anatomy of cycles of displacement.